Wpływ obrazu emocjonalnego na tor ruchu: rola znaczenia i siły kontekstu - Vilchez, Jose Luis (Neuropsychiatria i Neuropsychologia/Neuropsychiatry and Neuropsychology, 2017)
Aim of the study: The present study tests the effect of the attention to emotional content on movement trajectory. Methods: Pictures with positive and negative valence were presented on both sides of a simulated road in a driving-simulation tracking task for a series of two experiments for a total of 28 participants. Results: Both the approach and withdrawal effects toward/from the position in which emotional cues appeared have been found on the participants’ trajectory. In contrast to previous literature and common-sense hypotheses, these effects depended on the picture-presentation setting more than on their emotional valence. Some predictions in the literature pointed to finding approach movements for positive pictures and withdrawal behaviours for negative valences. In this sense, only negative pictures presented in close positions on the left-side of the road have been found to provoke approach tendencies. Conclusions: The “emotional”, right hemisphere processed picture presentations on the left side. Since it is impossible to select negative emotional pictures that do not have high emotional arousal, results point out to pictures arousal as the cause of the effects found. These findings are discussed under the perspectives of hemisphere laterality and models of motor control. The present study supports the MDRA model in its premise about how context can modify the meanings of attentional cues and, in turn, their impact on movement programming.